Craniomaxillofacial Trauma in Dogs—Part I: Fracture Location, Morphology and Etiology - De Paolo, Mercedes H.; Arzi, Boaz; Pollard, Rachel E.; Kass, Philip H.; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2020)
Treatment of craniomaxillofacial (CMF) trauma in dogs often requires a multidisciplinary approach and a thorough understanding of the CMF skeletal structures involved. The aim of this retrospective study was to use a large number of CT studies of dogs evaluated for CMF trauma and to describe fracture location and morphology in relation to demographic data and trauma etiology. The medical records and CT studies of 165 dogs over a 10-year period were evaluated. The skeletal location of CMF fractures as well as the severity of displacement and fragmentation of each fracture was recorded. Patient demographic data and trauma etiology were also recorded. Animal bites accounted for the majority of trauma (50%), followed by unknown trauma (15%), vehicular accidents (13%), and blunt force trauma (13%). Small dogs, <10 kg, and juveniles accounted for the majority of patients (41.8 and 25.5%, respectively). The most likely bone or region to be fractured was the maxillary bone, followed by the premolar and molar regions of the mandible. Up to 37 bones or regions were fractured in any given patient, with an average of 8.2 fractured bones or regions per dog. The most commonly fractured location varied according to trauma etiology. Specifically, vehicular accidents tended to result in more locations with a higher probability of fracture than other trauma types. A major conclusion from this study is that every bone of the CMF region was fractured in at least one case and many cases had a large number of fractured regions. Thus, the need for comprehensive assessment of the entire CMF region, preferably using CT, is underscored.